2009
DOI: 10.3109/03093640903171010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Patellar Tendon in Transtibial Amputees

Abstract: This study aimed to provide sonographic imaging of the patellar tendon (PT) -one of the main weight bearing structures for prosthetic use -in transtibial amputees. Thirteen males, who had been under follow-up for unilateral traumatic transtibial amputations, were enrolled. After physical examination of the limb, pain was evaluated by visual analogue scale and Leeds Assessment of Neuropathic Symptoms and Signs. Sonographic evaluations were performed by using a linear array probe (Aloka UST-5524-7.5 MHz) on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Further, tendons are force-transmitting units of the Elbow problems in spinal cord injury B Erhan et al musculoskeletal system and due to their low metabolic rate and slow healing, chronic overuse injury may cause structural changes and impact on tendons and peripheral soft tissues. 6 During weight-relief lifting activities, high-to-moderate muscular demands were documented on long head of triceps muscle besides latissimus dorsi and sternal pectoralis muscle. 7,8 Although previous reports have explored shoulder injuries in SCI, 3,9-12 the elbow joint, which serves as one of the main biomechanical units during the daily activities of paraplegic patients, has not been substantially evaluated in the relevant literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, tendons are force-transmitting units of the Elbow problems in spinal cord injury B Erhan et al musculoskeletal system and due to their low metabolic rate and slow healing, chronic overuse injury may cause structural changes and impact on tendons and peripheral soft tissues. 6 During weight-relief lifting activities, high-to-moderate muscular demands were documented on long head of triceps muscle besides latissimus dorsi and sternal pectoralis muscle. 7,8 Although previous reports have explored shoulder injuries in SCI, 3,9-12 the elbow joint, which serves as one of the main biomechanical units during the daily activities of paraplegic patients, has not been substantially evaluated in the relevant literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several demographical and clinical factors may affect the joints, tendons and peripheral neurons of patients who overuse their extremities. 6 Dudley-Javoroski et al, 13 showed the effect of the increasing weight among SCI patients on the achilles tendon in a controlled study with normal population. We found relationship between BMI and the right tendon thickness; this can be explained by the increase of TTT with the increasing BMI, similar to the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the comparisons of tendon thickness in trans-tibial amputees between our work and existing literature, our findings did not agree with the results reported by Ozcakar et al . 11 showing that the tendon thickness on the residual limb is greater than that of the intact limb. The inconsistent findings between our work and Ozcakar et al .’s study may be explained by different age (Ozcakar et al .…”
Section: Discussionmentioning
confidence: 98%
“…Although these patellar tendon morphological abnormalities may develop in amputees using a prosthesis with a PTB feature, there is limited evidence to support a correlation. To date, only one preliminary study revealed that the patellar tendon is thicker in the residual limb of trans-tibial amputees 11 . However, there have been no comparisons of neovascularity and intra-tendinous and gross morphological changes in the patellar tendon between trans-tibial amputees using a PTB design and healthy controls.…”
Section: Introductionmentioning
confidence: 99%